Assessment of the state of synergies between the structural and functional characteristics of the kidneys and liver during external use of a seaweed product Laminaria algae - Smirnov, I.; Nasibullin, B.; Gushcha, S. (Journal of Education, Health and Sport, 2024)
The authors conducted studies to study the relationship between the functional activity of the kidneys, the detoxification activity of the liver and the structural features of the parenchymatous tissue of these organs under normal conditions and with external use of the laminar algae product “Lamidan”. The work was performed on 164 white outbred Wistar rats weighing 180-200 g. The work was carried out in accordance with current standards for working with laboratory animals. The results of many years of research have shown that normally the indicators of detoxification activity of the liver and functional activity of the kidneys practically do not change, and they correspond to the structural organization of the parenchymatous tissue of these organs, corresponding to the descriptions given in well-known manuals on the activities of these organs. The use of "Lamidan" activates the detoxification function of the liver by 28 % and the functional activity of the kidneys by 28.5 %, i.e. changes are unidirectional and proportionate. In the parenchyma of both organs, changes in the structural organization are recorded, characteristic of an increase in functional activity. Thus, there is a strictly interrelated set of stereotypical changes in the indices of the two organs under study, reflecting between the organs interrelations of functional systems.